Riverside : selectors : Peter Doig, Roy Arden 1999, Keith Piper, Sebastian Lopez 2000. - Morris, Lynda (Norwich : Norwich University of the Arts, 2000)
Doig, Peter ; Arden, Roy ; Piper, Keith ; Lopez, Sebastian ; Cornford & Cross ; Wright, Elizabeth ; Berge, Kjetil ; Niscino, Tazro ; Woolford, Tom ; Rook, Anne ; McBride, Christina ; Schmacke, Claudia ; Chinneck, James ; Pope, Nina ; Guthrie, Karen
Riverside : selectors : Peter Doig, Roy Arden 1999, Keith Piper, Sebastian Lopez 2000, Norwich Gallery - Norwich School of Art and Design Norwich, 2000
Engels
boek